The University of California San Francisco (UCSF) Training Program in Implementation Science: Program Experiences and Outcomes - Shete, Priya B.; Gonzales, Ralph; Ackerman, Sara; Cattamanchi, Adithya; Handley, Margaret A. (Frontiers in Public Health, 2020)
Purpose We evaluated outcomes of trainees who have completed Certificate program in Implementation Science at the University of California San Francisco. Methods All students who completed the in-person Certificate Program (2008-2015), or the online Certificate Program (2016-2017) were eligible for our study. We assessed the potential impact of the Certificate Program on the professional development of trainees, through participant surveys on their self-reported level of comfort with pre-defined competencies and on academic productivity. Results Of eligible trainees, 54 in-person (77%) and 13 online (100%) Certificate Program participants completed surveys. In-person trainees reported a total of 147 implementation science-related publications in peer-reviewed journals (median 3 publications/trainee, IQR 1-15). Thirty-four trainees (63%) reported being a Principal Investigator (PI) of 64 funded implementation science-related grants (median 2 grants/trainee, IQR 1-4). 15% (n=8) of participants reported receiving an NIH grant on which they were the PI, including R01 or P01 level funding (n= 4, 7%) and K awards (n=3, 6%). Both in-person and on-line trainees reported median high to moderate confidence for all 12 competencies assessed. Confidence waned in skills aligning with later stages of implementation research for all trainees. Conclusion The moderate to high confidence in all competencies assessed and reported high level of academic productivity support the benefits of intensive, graduate-level training focused on applied methods to support career development of implementation scientists.